When f(x)=x^2-1 and g(x)=x+2 If someone could help me with first step I could probably do the rest. Thanks,
Follow Math Help Forum on Facebook and Google+
Hi! Try sticking the expressions for $\displaystyle g(x) $into the place of the x in the expression of $\displaystyle f(x)$. $\displaystyle f(g(x))=(x+2)^2-1 $. Hope this helps... I'm not mathematician.
Originally Posted by Tally When f(x)=x^2-1 and g(x)=x+2 If someone could help me with first step I could probably do the rest. Thanks, $\displaystyle g(-3) = -3+2 = -1$ $\displaystyle f(g(-3))= (-1)^{2} -1 = 1-1 = 0$
Originally Posted by harish21 $\displaystyle g(-3) = -3+2 = -1$ $\displaystyle f(g(-3))= (-1)^{2} -1 = 1-1 = 0$ Awesome Thank you. I understand it much clearer now.
View Tag Cloud